Japananoides, a new leafhopper genus from China (Hemiptera: Cicadellidae: Deltocephalinae) - Cao, Wenjun; Xing, Jichun (Zootaxa, 2022)
A new genus of the tribe Opsiini from China, Japananoides gen. nov. with J. circularis sp. nov. as type species is described and illustrated. A new synonymy is also proposed: Pseudophlepsius binotatus (Signoret, 1880) equals Phlepsopsius liupanshanensis Li, 2011 syn. nov. A checklist and key to Chinese genera of Opsiini are provided. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).